Character Education Management in Realizing the Student Profile of Rahmatan Lil Alamin at Ma Al-Azhar Ash-Syarif North Sumatra - Andi Suhendra Siregar; Amiruddin Siahaan; Zaini Dahlan (Journal of General Education and Humanities, 2026)
Character education plays an essential role in shaping students' character in line with the Rahmatan Lil' Alamin student profile within Islamic educational institutions, particularly madrasahs that integrate religious values into daily learning practices. However, its implementation still faces challenges related to consistency, value integration, and effectiveness within the boarding school environment, requiring a comprehensive analysis of planning, implementation, and evaluation processes. This study aims to analyze the planning, implementation, evaluation, as well as supporting and inhibiting factors of character education at MA Al-Azhar Ash-Syarif North Sumatra. This study employs a qualitative field research design. Data were collected through interviews, observations, and documentation involving key informants, school activities, and institutional records. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings show that character education planning is conducted comprehensively through needs identification and value integration in madrasah programs. Implementation occurs within the boarding school ecosystem through habituation, role modeling, and supervision. Evaluation is carried out using assessment instruments, classroom observations, digital report cards, and feedback from students and parents. Supporting factors include a strong religious culture, adequate infrastructure, and solid institutional management, while challenges include the influence of digital technology and variations in parenting patterns. The study concludes that the implementation of character education at MA Al-Azhar Ash-Syarif North Sumatra is effective in realizing the Rahmatan Lil' Alamin student profile through a structured, sustainable system. The study contributes theoretically to character education in Islamic boarding school contexts, while practically providing insights for strengthening integrated character education systems and highlighting the need for institutional support in managing digital influence and parental involvement.